(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
This article investigates the theoretical and methodological foundations of contrastive linguistics as a dynamic field of modern linguistic science. It explores the evolution of contrastive studies from their didactic and pedagogical origins in the mid-twentieth century to the typologically and cognitively grounded approaches of the contemporary era. The paper highlights how the principles of cross-linguistic comparison contribute to identifying structural, semantic, and functional differences across languages. Special attention is given to the analysis of formal and functional domains of contrastive research, including phonological comparison (consonant inventory) and syntactic analysis (extraction operations). The study demonstrates that variations in syntactic movement between English and German reveal deeper typological distinctions between analytic and synthetic languages. Furthermore, the article emphasizes the growing significance of corpus-based approaches in contrastive linguistics, as they ensure the empirical accuracy and reproducibility of linguistic data. It is concluded that contrastive linguistics occupies an intermediate position between theoretical and applied branches of linguistic research, supporting the development of translation studies, foreign language pedagogy, and intercultural communication